2019
DOI: 10.4196/kjpp.2019.23.4.251
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol exerts anti-asthmatic effects by regulating Janus kinase-signal transduction and activation of transcription and Notch signaling pathways and modulating Th1/Th2/Th17 cytokines in ovalbumin-sensitized asthmatic mice

Abstract: Allergic asthma, is a common chronic inflammatory disease of the airway presenting with airway hyperresponsiveness and airway remodelling. T helper cells-derived cytokines are critically associated with asthma pathogenesis. Janus kinase-signal transduction and activation of transcription (JAK/STAT) signaling is found to be involved in asthma. Magnolol is a plant-derived bioactive compound with several pharmacological effects. The study aimed to assess the effects of magnolol in ovalbumin (OVA)-induced asthmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…e study also found that the counts of inflammatory eosinophils, neutrophils, and lymphocytes of the BALF of asthma mice in the OVA + MDSCs group increased, and macrophages were reduced relative to the OVA group. It was similar to the Huang et al's study that neutrophils and their related inflammatory factors played an increasingly vital role in asthma, and there was also an increase in neutrophils in the asthma model [24].…”
Section: Discussionsupporting
confidence: 83%
“…e study also found that the counts of inflammatory eosinophils, neutrophils, and lymphocytes of the BALF of asthma mice in the OVA + MDSCs group increased, and macrophages were reduced relative to the OVA group. It was similar to the Huang et al's study that neutrophils and their related inflammatory factors played an increasingly vital role in asthma, and there was also an increase in neutrophils in the asthma model [24].…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, we have observed that treatment with the γ-secretase inhibitor DAPT, which blocks NOTCH activation, inhibited the Th17 immune response and downstream inflammatory response in obstructed kidneys. Our findings extend to renal diseases the previous studies describing that NOTCH inhibition diminished the Th17 immune response in the experimental models of allergic asthma, 59 and autoimmune encephalomyelitis. 35 Interestingly, although in injured kidneys there is a markedly upregulation of many proinflammatory genes, only Ccl2 (encoding MCP-1) was significantly upregulated in Dlk1-null mice compared to WT mice.…”
Section: F I G U R Esupporting
confidence: 87%
“…Indeed, there is some evidence from other studies in OVA‑sensitized mice that inhibiting the JAK/STAT pathway may suppress Th1 and Th17 signaling. 56 , 57 Our data do not rule out the possibility that AZD0449 and AZD4604 have an effect on non-type 2 asthma phenotypes, suggesting broad applicability for selective inhaled JAK1 inhibitors, but further studies are required to explore this potential.…”
Section: Discussionmentioning
confidence: 73%